2003
DOI: 10.1161/01.hyp.0000087889.60760.87
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Angiography Is the Best Predictor of Events in Renal Transplant Candidates Compared With Noninvasive Testing

Abstract: Abstract-Guidelines for the detection of coronary artery disease (CAD) and assess of risk in renal transplant candidates are based on the results of noninvasive testing, according to data originated in the nonuremic population. We evaluated prospectively the accuracy of 2 noninvasive tests and risk stratification in detecting CAD (Ն70% obstruction) and assessing cardiac risk by using coronary angiography (CA). One hundred twenty-six renal transplant candidates who were classified as at moderate (Ն50 years) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
151
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(164 citation statements)
references
References 26 publications
7
151
0
6
Order By: Relevance
“…16 The high LVH rate we found confirmed the data reported by Kundhal et al, 18 who observed LVH in 74% of the dialysis population. There are several factors implicated in the development of LVH in the CKD population, such as arterial thickening (due to alterations of the calcium, phosphorus, PTH and vitamin D metabolism) and systolic hypertension (due to a chronic state of hypervolemia and anemia-related increased after-load).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…16 The high LVH rate we found confirmed the data reported by Kundhal et al, 18 who observed LVH in 74% of the dialysis population. There are several factors implicated in the development of LVH in the CKD population, such as arterial thickening (due to alterations of the calcium, phosphorus, PTH and vitamin D metabolism) and systolic hypertension (due to a chronic state of hypervolemia and anemia-related increased after-load).…”
Section: Discussionsupporting
confidence: 91%
“…These peculiarities, among others, make the cardiovascular assessment of CKD patients a particularly difficult task. In spite of the high rate of electrocardiographic abnormalities found, which is in agreement with the literature data, 16 there was no significant difference between Groups A and B. This decreases the importance of electrocardiography for the cardiac assessment of CKD patients.…”
Section: Discussionsupporting
confidence: 90%
“…Screening was done by the CRF specialized outpatient unit at the Hypertension Service, Heart Institute, University of São Paulo at São Paulo. In that service, the management of high risk patients or patients with suspicion of CAD includes ICA for its better prognostic performance 7 . Nonionic iodinated contrast was performed after the exclusion of contra-indication to the study and after the informed consent was signed.…”
Section: ) Diabetes Mellitus;mentioning
confidence: 99%
“…Therefore, they must be submitted to invasive diagnostic procedure 6 . As for CAD evaluation strategies for those patients and their association to prognosis, De Lima et al 7 have published conclusive data showing that invasive coronary angiography (ICA) proved to be of higher prognostic value for CAD evaluation when compared to non-invasive tests (nuclear medicine and stress ECG) 7 . That paved the way for the investigation of new noninvasive diagnostic methods not yet under use for this group of CRF patients and which had been showing good performance in CAD patients in the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation